2021
DOI: 10.1007/s00068-021-01643-x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced phagocytosis, ROS production and enhanced apoptosis of leukocytes upon alcohol drinking in healthy volunteers

Abstract: Background Alcohol drinking is associated with a serious risk of developing health problems as well as with a large number of traumatic injuries. Although chronic alcohol misuse is known to contribute to severe inflammatory complications, the effects of an acute alcohol misuse are still unclear. Here, the impact of acute alcohol drinking on leukocyte counts and their cellular functions were studied. Methods Twenty-two healthy volunteers (12 female, 10 male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…In addition, low ROS concentration can promote cell proliferation, whereas excessive ROS levels cause DNA oxidative damage, consequently inducing cell death [ 105 ]. ROS levels are implicated in all blood cell lines death: platelets [ 106 , 107 ], RBCs [ 108 , 109 ], and WBCs [ 110 , 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, low ROS concentration can promote cell proliferation, whereas excessive ROS levels cause DNA oxidative damage, consequently inducing cell death [ 105 ]. ROS levels are implicated in all blood cell lines death: platelets [ 106 , 107 ], RBCs [ 108 , 109 ], and WBCs [ 110 , 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the immunosuppressive effect of alcohol seems to affect the functionality of individual monocyte subsets without changing their ratios at T48. In line with this, less monocytes are positive for reactive oxygen species at 48 hours after binge drinking, suggesting lower antimicrobial competence (25). Acute alcohol intoxication-related decrease in TLR4 response, so-called TLR4 tolerance, is induced by B-cell lymphoma 3-encoded protein (Bcl-3) that negatively regulates TNF-a transcription (34).…”
Section: Discussionmentioning
confidence: 67%
“…Regarding the delayed increase of the relative nonclassical monocyte fraction, it seems, that alcohol intoxication converts the intermediate into non-classical monocytes and thereby, switch their pro-inflammatory character into an immunosuppressive cell type. Under the same experimental settings, it has been shown that absolute leukocyte numbers significantly increase two and four hours after starting alcohol drinking, suggesting an early mobilization of immune system (25). The percentage of granulocytes out of all leukocytes decreases significantly at four and six hours, whereas the monocyte percentage decreases first significantly at six hours with subsequent significant elevation at 24 and 48 hours postdrinking (25).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations